Teaching English in preschool age selection of methods and techniques - Magdalena Bojar (Language, Culture, Politics)
The main purpose of this article is to present methods and techniques that can be used in the process of teaching a foreign language at preschool age. The rst aspects to be addressed are developmental features of children, such as mechanical memory, short attention span, emotions and physiology of brain. The following issue described in the article refers to conventional methods, such as the Direct Method and the Audiolingual Method. The third part is devoted to unconventional methods, such as the Natural Approach, CLT, the Spiral Language System, as well as methods based on action (TPR), or observation and words. They are supported by interesting techniques that are considered key factors in the discussed topic.